(untitled) (CIPEEX, 2025)
This paper examines the five-year limitation period for the judicial collection of taxes subject to official assessment, counting from the definitive assessment of the tax credit; it adopts a doctrinal approach combined with case-law analysis. It aims to delineate the starting point under Article 174 of Brazil’s National Tax Code (CTN), the effects of pending administrative proceedings on the running of the period, and the statutory grounds for interruption, as well as to assess impacts for taxpayers and the Treasury. Methodologically, it relies on a literature review, analysis of applicable legislation, and a survey of Superior Court of Justice precedents, focusing on the ratio decidendi and practical consequences. The findings indicate a consolidated understanding that the limitation period begins only after the tax credit becomes definitive and does not run during administrative litigation; once enforcement acts commence, the period may be interrupted on statutory grounds. Overall, the framework enhances predictability, legal certainty, and collection efficiency, provided that deadlines and procedural requirements are observed. It concludes that fixing the starting point at the definitive assessment, together with interruption rules, balances taxpayer protection against indefinite claims with the tax authority’s duty of diligence.